Sexual and reproductive health and women development from a gender perspective: The role of men - Ragúz, María (2000)
Women's health, particularly, sexual and reproductive health, and development are here approached from a gender and human rights perspective, underlying the need to address these problems from a relational and comprehensive point of view. The issue of how sexual and reproductive health is approached and the "men's as partners" strategy is discussed. Adult women-centered, female-only family planning reproduction and contraception are criticized. Gender violence eradication is stressed as an entry to sexual and reproductive health programs. The case of Peruvian urban and rural women in poverty from Amazonian and Andean communities is taken as an example. Obstacles and achievements in working with men are reviewed but a gender transversal perspective is highlighted. Finally, women's sexual and reproductive health is related to development and seen as a standpoint for addressing health.